EKSPLORASI ETNOMATEMATIKA MUSEUM PUSAKA KARO DI KABUPATEN KARO - Rizqi, Nur Rahmi; Maharani, Israq; Ramadhani, Ramadhani (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
Mathematics and culture can be combined to make learning more innovative, enjoyable and at the same time getting to know the culture around you better. Ethnomathematics is a forum that bridges mathematics with the surrounding cultural context. This research aims to describe the results of the exploration of the concept of ethnomathematics at the Karo Heritage Museum, especially regarding spatial and flat shapes found in historical objects at the Karo Heritage Museum so that it can be used as a learning resource for students. The type of research used is qualitative research with an ethnographic approach. Data collection methods include observation and documentation. The results of the research show that there is an ethnomathematics exploration of historical objects in the Pusaka Karo museum, especially mathematical concepts which can be used as a contextual learning resource in schools.